The Gateway to Computer Science Excellence
First time here? Checkout the FAQ!
x
0 votes
654 views
8. Let P and Q be two propositions, ¬ (P ↔ Q) is equivalent to :

(1) P ↔ ¬ Q

(2) ¬ P ↔ Q

(3) ¬ P ↔ ¬ Q

(4) Q → P
in Mathematical Logic by (393 points)
retagged by | 654 views
0
3..?
0

can u explain how option 3 @  MiNiPanda

0
p<->q means (p->q)•(q->p)

= (!p+q)(!q+p) = p xnor q.

From the options given you can check that option 1 and 2 will give (p xor q) and last one will give (!q+p). Only option 3 is giving pxnorq.

1 Answer

+3 votes
Best answer

$¬(P\leftrightarrow Q)$

$ ¬(P\rightarrow Q \wedge Q\rightarrow P)$

$¬ ((\bar{P}\vee Q) \wedge (\bar{Q}\vee P))$

$¬(\bar{P}\bar{Q} \vee PQ)$

$¬(P \odot Q)$

$(P\oplus Q)$

now check which options looks like XOR 

P $\bar{P}$ Q $\bar{Q}$ $\bar{P} \leftrightarrow Q$ $P \leftrightarrow \bar{Q}$
T F T F F F
T F F T T T
F T T F T T
F T F T F F

$\bar{P} \leftrightarrow Q$ and $P \leftrightarrow \bar{Q}$ both are correct

by Boss (35.1k points)
edited by

Related questions

Quick search syntax
tags tag:apple
author user:martin
title title:apple
content content:apple
exclude -tag:apple
force match +apple
views views:100
score score:10
answers answers:2
is accepted isaccepted:true
is closed isclosed:true
50,288 questions
55,719 answers
192,111 comments
90,121 users